2019
DOI: 10.3390/molecules24040689
|View full text |Cite
|
Sign up to set email alerts
|

A Chemiluminescent Method for the Detection of H2O2 and Glucose Based on Intrinsic Peroxidase-Like Activity of WS2 Quantum Dots

Abstract: Currently, researchers are looking for nanomaterials with peroxidase-like activity to replace natural peroxidase enzymes. For this purpose, WS2 quantum dots (WS2 QDs) were synthesized via a solvothermal method, which improved the mimetic behavior. The resulting WS2 QDs with a size of 1–1.5 nm had a high fluorescence emission, dependent on the excitation wavelength. WS2 QDs with uniform morphology showed a high catalytic effect in destroying H2O2. The peroxidase-like activity of synthesized nanostructures was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 60 publications
(58 reference statements)
0
26
0
Order By: Relevance
“…Luminol is the luminescence agent compared with most previously published methods. [7,10,[32][33][34] This result indicated that Fe-PorCOF was a good catalyst for the luminol reaction.…”
Section: Influence Of Experimental Conditions On the Reactionmentioning
confidence: 78%
“…Luminol is the luminescence agent compared with most previously published methods. [7,10,[32][33][34] This result indicated that Fe-PorCOF was a good catalyst for the luminol reaction.…”
Section: Influence Of Experimental Conditions On the Reactionmentioning
confidence: 78%
“…[12][13][14] Along with their multipurpose applications mentioned above, nanochannels have been widely used for sensing smallmolecules, proteins, [15] DNA, [16] and bacteria using optical methods based on reflecto metric interference spectroscopy (RIS), surface plasmon reso nance (SPR), and photoluminescence. [17,18] Moreover, various electrochemical based sensors using nanomaterials and nano channels have been developed, including amperometry, voltam metry, impedance, conductivity, and resistivity functions. [19][20][21][22][23][24] Biosensing and sensing systems can be commercially devel oped for multiple applications to monitor environmental pol lutants, detect pathogens, measure clinical parameters [25][26][27] etc.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Among the classical analytical methods, chemiluminescence, spectrophotometry and high performance liquid chromatography (HPLC) have been widely used for H 2 O 2 detection. [6][7][8][9][10][11] Besides the classical analytical methods, electrochemical sensors and biosensors allow the development of time saving, accurate and cost-effective H 2 O 2 detection methods. [12][13][14][15][16][17] Among enzyme based electrochemical biosensors, the ones based on direct electron transfer (DET) between the enzyme and the electrode exhibit many advantages, such as high selectivity, either because of a small overpotential is needed to activate the oxidation/reduction process or due to the lack of extra reagents (e. g., diffusing or immobilized mediators etc.).…”
Section: Introductionmentioning
confidence: 99%
“…), high H 2 O 2 concentrations are considered toxic for humans [4,5] . Among the classical analytical methods, chemiluminescence, spectrophotometry and high performance liquid chromatography (HPLC) have been widely used for H 2 O 2 detection [6–11] . Besides the classical analytical methods, electrochemical sensors and biosensors allow the development of time saving, accurate and cost‐effective H 2 O 2 detection methods [12–17] …”
Section: Introductionmentioning
confidence: 99%